A case report: Early findings of distal vessel occlusion pre and post-thrombolysis using three-dimensional black blood vessel wall imaging in acute stroke. - Kamis, Mohd Fandi Al Khafiz; Peck Kee, Chia; Mohd Yaakob, Mohd Naim; Abdul Rahim, Ezamin; Muda, Ahmad Sobri; Mohd Sabri, Mohd Naqib; Abd Ghani, Fatimatulzahra (Journal Of Cardiovascular, Neurovascular & Stroke, 2021)
Distal vessel occlusion of an eloquent area in acute stroke may lead to significant disability. Advances in magnetic resonance imaging enable direct visualization of thrombus within the small distal intracranial artery. The evolution of medical devices for mechanical thrombectomy has allowed the smaller distal vessels to be treated. It may change the approach to how we treat distal vessel occlusion in the future. This case highlights the value of three-dimensional black blood vessel wall imaging assessing distal vessel occlusion and respond towards reperfusion therapy.